PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PERUBAHAN WUJUD ZAT MENGGUNAKAN MEDIA PEMBELAJARAN SENSOR PANAS MELALUI PENDEKATAN PEMBELAJARAN STEM (SCIENCE, TECHNOLOGY, ENGINEERING, AND MATHEMATICS) DI SD NEGERI DAWUHAN 3 SITUBONDO TAHUN PELAJARAN 2015/2016 - Moh. Nuril Hudha (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2015)
In fact, most teachers teaching and learning activities in the classroom tend to be conventional. This means in transforming science, teacher using the lecture method so that the learning-centered teachers and students are less able to link the existing chemical science concepts into daily life. To overcome these problems, it is necessary an approach to learning that can be used to create a more active learning. One way is to apply the approach to STEM (Science, Technology, Engineering and Mathematics). This study was to determine the role of learning media heat sensors to achieve basic competence in the matter Being a change agent, and to improve student learning outcomes in completeness Being a change agent material after applying practical use of instructional media heat sensors using STEM learning approach. In this study used data analysis is qualitative descriptive analysis. The data analyzed are learning achievement test scores in the material chemistry Being a change agent and observational data activities of teachers and students in learning activities using STEM learning approach. Class VI student learning outcomes cognitively in cycle 1 in classical amounted to 75.76% and in the second cycle in classical learning completeness of 90.90%, so an increase of 15.14%. It has achieved the goal of this research is the role of the completeness of student learning outcomes after applying the practical use of instructional media heat sensors using STEM learning approach has been reached.